Policy implications of cultural shifts and enduring low fertility in Iran - Amir Erfani (Shahid Beheshti University of Medical Sciences, 2019)
Fertility levels have fallen drastically to a below-replacement level (under two children per woman required to maintain the population) in most developed and some developing countries, including Iran. Over the past two decades, the total fertility rate of Iran (the average number of children per woman) has remained under the replacement level, dropping from 2.0 children per women in 2000 (1) to 1.8 in 2005 and then to 1.6 in 2018 (2,3). The persistent low fertility rate is an increasing concern for countries with low fertility, as it accelerates population ageing and declining labor force, with the prospect of severe consequences for economic development. As a result, increasing attention is being paid to policies to reduce the socioeconomic burdens of low fertility. These policies can be efforts to reverse declining fertility or to adapt to low fertility trends. The pronatalist efforts include positive measures, such as raising economic incentives and lowering costs of additional births, and negative measures that limit access to fertility control. However, increasing fertility through government intervention has been far more difficult and costly, than inducing a fertility decline, with minimal effect on raising fertility in many Western countries, and the application of negative measures in the past resulted in a temporary short-lived fertility rise along with a sharp rise in maternal morbidity and mortality, related to unintended pregnancies terminated by unsafe abortions. A recent example of the negative measures is the limitation in the government-funded family planning services in Iran that largely affected women from low socioeconomic status with large number of children (4), with minimal effect on raising fertility, because the publicly-funded contraceptive methods contributed to only 7% of the country's fertility decline (5). Due to the minimal success of the pronatalist policies, many low-fertility nations decided to adapt their age-related social services, such as health-care, social security and retirement and education systems, to a low-fertility regime and aging population structure by taking measures such as raising retirement age, admitting immigrants and adjusting education, tax and health systems. For different political and economic reasons, Iran is not yet ready to apply any adapting measures. Therefore, for adequate policy responses to the country's persistent below-replacement fertility, a thorough understanding of the formation of a person's fertility intention, which is viewed as a key predictor of fertility behaviour, is essential. In the article, "Reasons for intending to have no children in Tehran, Iran", published in the current issue of Journal of Community Health, Erfani and his colleague showed that after economic and parity-related reasons, "conflict of childbearing with own personal life, plans and interests" and "being worry about the future of their children"standout as the two most important social and cultural reasons for not wanting any (more) children. The other results of this study showed that these cultural reasons reported  largely from those with higher levels of education and income, and having one or no child, suggesting that their low fertility intention is attributed to socio-cultural reasons rather than economic factors. These findings as well as evidence from other Iranian studies, stated below, are clear evidence for the fact that Iran has entered into a Second Demographic Transition, which relates low fertility to cultural shifts from traditional familial values toward individualization of moral norms and values, which occurred first in Europe, spread to North America and now to Asia (6). In fact, the emerging individualistic norms place less value on marriage and the family unit, and embrace alternate forms of family, including single parent, cohabitation, divorce, and childless family. Further evidence from recent Iranian studies have documented the emergence of such cultural changes, including the growth of materialistic values and individualism (7), rising childless or one-child families, delaying marriage and family formation, rising divorce rates and falling marriage rates, growing abortion rates (8), increasing premarital sex and cohabitations and positive attitudes toward premarital dating and sexual encounters. Therefore, individualism is the base for low fertility, as individuals give priority to their "well-being and self-expression", choose their own partners and their desired form of relationship and number of children, and make family and childbearing decisions based on their self-interests. Consequently, if the government decides to employ any pronatalist measures to increase fertility in the country, it is absolutely necessary to bring into its calculation the recent cultural shifts to individualistic values and norms that affect individuals' childbearing decision-making. DOI: http://doi.org/10.22037/ch.v6i2.23366.